Th1/M1 Conversion to Th2/M2 Responses in Models of Inflammation Lacking Cell Death Stimulates Maturation of Monocyte Precursors to Fibroblasts - Trial, JoAnn; Cieslik, Katarzyna A.; Haudek, Sandra B.; Duerrschmid, Clemens; Entman, Mark L. (Frontiers in Immunology, 2013)
We have demonstrated that cardiac fibrosis arises from the differentiation of monocyte-derived fibroblasts. We present here evidence that this process requires sequential Th1 and Th2 induction promoting analogous M1 (classically activated) and M2 (alternatively activated) macrophage polarity. Our models are 1) mice subjected to daily repetitive ischemia reperfusion (I/R) without infarction and 2) the in vitro transmigration of human mononuclear leukocytes through human cardiac microvascular endothelium. In the mouse heart, leukocytes entered after I/R in response to monocyte chemoattractant protein-1 (MCP-1) which is the major cytokine induced by this protocol. Monocytes within the heart then differentiated into fibroblasts making collagen while bearing the markers of M2 macrophages. T cells were seen in these hearts as well as in the human heart with cardiomyopathy. In the in vitro model, transmigration of the leukocytes was likewise induced by MCP-1 and some monocytes matured into fibroblasts bearing M2 markers. In this model, the MCP-1 stimulus induced a transient Th1 and M1 response that developed into a predominately Th2 and M2 response. An increase in the Th2 product IL-13 was present in both the human and the mouse models, consistent with its known role in fibrosis. In these simplified models, in which there is no cell death to stimulate an anti-inflammatory response, there is nonetheless a resolution of inflammation enabling a profibrotic environment. This induces the maturation of monocyte precursors into fibroblasts.